Intellectual Extremism and Its Impact on Societal Peace - Ghaidaa Jalal Shihab,; Khayal Saleh Hamad, (Islamic Sciences Journal, 2025)
This research addresses the phenomenon of intellectual extremism and its impact on societal peace, highlighting that extremism leads to increased tensions and divisions within society. The research presents the causes behind this phenomenon, such as ignorance, intolerance, and poverty, and discusses the role of the media in spreading extremist ideas. It also emphasizes the importance of promoting values of tolerance and moderation as solutions to counter extremism and stresses the necessity of enhancing dialogue and intellectual awareness within communities to reduce the impact of extremism on social stability.